First and second-year sea-ice dissolved inorganic carbon and total alkalinity from the coring site during MOSAiC legs 1 to 5 in 2019/2020 - Daiki Nomura; Masaki Yoshimura; Jessie Creamean; Lena Eggers; Laura Heitmann; Adam Ulfsbo; Clara Jule Marie Hoppe; Jessie Gardner; Emelia Chamberlain; Elise Sayana Droste; Allison A Fong; Agneta Fransson; et al. (PANGAEA, 2025)
First- and second-year sea-ice core sampling for dissolved inorganic carbon (DIC) and total alkalinity (TA) were examined during MOSAiC legs 1 to 5 in 2019/2020 at main coring sites on the first ice floe (legs 1–4) and on the second ice floe (leg 5). See Fong et al. (2024) for details on sampling strategy. Ice cores were collected using an ice corer (Mark II coring system, Kovacs Enterprises, Inc., Indianapolis, USA). Ice cores were segmented at 10-cm intervals. Ice sections were placed into gas tight bags (Smart bags PA, AAK 5L, GL Sciences Inc., Japan or 5L Tedlar and Kynar Bags with Poly 2-in-1 Valve and clip extquotesinglen seal, Keika Ventures, Chapel Hill, USA), air within the bag was removed, and ice melted in the dark at +4°C. Then, ice meltwater was subsampled into 200 mL glass vial (Maruemu Co., Ltd., Osaka, Japan) for measurement of DIC, TA, and salinity. Immediately after subsampling for measurement of DIC and TA, a 6.0% (wt.) mercuric chloride (HgCl2) solution (100 μL) was added to stop biological activity. Samples were stored at +4°C on the R/V Polarstern. For analysis, samples were transported to Hokkaido University, Hakodate, Hokkaido, Japan. Ice temperature data was shown in Oggier et al. (2024), Oggier et al. (2025), and Salganik et al. (2024). The DIC was determined by coulometry (Johnson et al., 1985; Johnson, 1992) using a home-made CO2 extraction system (Ono et al., 1998) and a coulometer (CM5012, UIC, Inc., Binghamton, NY, USA). The TA was determined by potentiometric titration (Dickson et al., 2007) using a TA analyzer (ATT-05, Kimoto Electric Co., Ltd., Japan). Both DIC and TA measurements were calibrated with reference seawater materials (Batch AR, AU, and AV; KANSO Technos Co., Ltd., Osaka, Japan) traceable to the Certified Reference Material distributed by Prof. A. G. Dickson (Scripps Institution of Oceanography, La Jolla, CA, USA). The standard deviations of the DIC and TA measurements, calculated from 10 subsamples taken from reference water with a DIC value of 2039.4 μmol kg-1 and a TA value of 2311.6 μmol kg-1, were ±1.4 μmol kg-1 and ±1.2 μmol kg-1, respectively. The salinity was determined by conductivity sensor (Cond 315i, WTW GmbH, Germany) from DIC and TA samples.